Electric field stimulation induced neuronal differentiation of filum terminale derived neural progenitor cells. (9th June 2017) - Dong, Zhi-yong; Pei, Zhe; Li, Zhe; Wang, Yan-ling; Khan, Amber; Meng, Xiao-ting
Highlights: We designed an EF setup and generated a protocol to help long-term differentiation induction. EFs significantly increase neuronal differentiation rate of FT derived NPCs. EFs align neurite outgrowth and promote the length of neurite processes. Abstract: Adult filum terminale (FT) is an atypical region from where multipotent neural progenitor cells (NPCs) have been isolated. However, poor neuronal differentiation rate of FT-NPCs currently limits their clinical applications. Using custom-designed electric fields (EFs), this study sets up a method to significantly improve neuronal differentiation rate of rat FT-NPCs in vitro . We investigated the influence of EF strength on rat FT-NPCs differentiation. By adding reasonable strength of EF to FT-NPCs, our data shows a significant increase in neuronal differentiation rate. The present innovation provides a novel method of directional differentiation and efficient production of neurons from FT-NPCs in vitro. This improved approach for inducing neuronal differentiation can be applied to future research on autoplastic transplantation.